Supply chain resilience: an empirical model - Carvalho, Helena Maria Lourenço (2019)
This research was funded by Fundação para a Ciência e Tecnologia (Project PTDC/EMEGIN/68400/2006 and Project MIT-Pt/EDAM-IASC/0033/2008). Helena Carvalho was supported by a PhD fellowship from Fundação para a Ciência e Tecnologia (SFRH/BD/43984/2008).